2009
DOI: 10.1186/1472-6963-9-154
|View full text |Cite
|
Sign up to set email alerts
|

Do computerised clinical decision support systems for prescribing change practice? A systematic review of the literature (1990-2007)

Abstract: Background: Computerised clinical decision support systems (CDSSs) are used widely to improve quality of care and patient outcomes. This systematic review evaluated the impact of CDSSs in targeting specific aspects of prescribing, namely initiating, monitoring and stopping therapy. We also examined the influence of clinical setting (institutional vs ambulatory care), system-or user-initiation of CDSS, multi-faceted vs stand alone CDSS interventions and clinical target on practice changes in line with the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 71 publications
5
115
0
6
Order By: Relevance
“…In another study, Subramanian et al (2007) found that the increasing use of CPOE has facilitated the "elimination of handwriting identification problems, reductions in error associated with similar drug names, faster delivery of orders to the pharmacy" (p. 1451). These studies and others from the literature affirm the significant impact of CDSS in reducing medical errors in clinical practice, thereby, improving the quality of care, patient safety, and patient outcomes (Pearson et al, 2009). …”
Section: Patient Safety and Outcomesmentioning
confidence: 65%
See 3 more Smart Citations
“…In another study, Subramanian et al (2007) found that the increasing use of CPOE has facilitated the "elimination of handwriting identification problems, reductions in error associated with similar drug names, faster delivery of orders to the pharmacy" (p. 1451). These studies and others from the literature affirm the significant impact of CDSS in reducing medical errors in clinical practice, thereby, improving the quality of care, patient safety, and patient outcomes (Pearson et al, 2009). …”
Section: Patient Safety and Outcomesmentioning
confidence: 65%
“…CDSS have been recognized as promising tools for influencing healthcare provider performance to improve and streamline the quality of healthcare delivery (Bassa et al, 2005;Pearson et al, 2009). CDSS originated from Decision Support Systems (DSS).…”
Section: Overview Of Clinical Decision Support Systems (Cdss)mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas present studies focus on the alert fatigue or so called false-positives, not reporting of important alerts may be even more serious. An important reason for not providing insight into underreporting comes from the fact that present studies do not directly compare manual medication surveillance with a CDSS in the same patient population, [28,29]. Controls usually consist of a different population or a historical cohort.…”
Section: Improving the Cdssmentioning
confidence: 99%